(untitled) (Pakistan Journal of Science, 2020)
Pigeons are omnipresent birds which belong to the order, Columbiformes and cover a large part of every town and city, worldwide. Among the parasites of pigeons, Capillaria is found to be more prevalent in them after Eimeria. These worms penetrate deeply in the intestinal mucosa leading to haemorrhages and epithelial necrosis thereby presenting clinical disease and death occurs if left untreated. The major purpose of this study was to determine the burden of Capillaria spp. in domestic pigeons (Columba livia domestica) of district Narowal. Total 210 fecal samples from pigeon flocks were processed qualitatively through direct microscopy and floatation method while quantitatively through McMaster technique. The parasitic eggs were diagnosed using standard keys. In this study, 154 (73.33%) out of the 210 samples were found infected with Capillaria spp. The quantitative examination presented the lowest eggs per gram (EPG) of 300 in the Narowal tehsil and highest EPG of 800 in Shakargarh tehsil among the study areas. This study will be helpful in raising awareness to pigeon owners to improve pigeons health status through better control of capillariasis.